(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
We analyze the advantages and disadvantages of developing a local, provincial price index, taking into account the greater transparency reached by INDEC as of 2016. We conclude that an index for La Pampa is justified given that its reality is not represented in the National index, and neither in the two Pampeano and Patagonian regional indexes that are prepared since mid-2017. It should be noted that the CPI of the Pampean region has a strong Buenos Aires bias in a historical period where the national government tries to correct the low rates of Buenos Aires compared to those existing in the interior of the country. New price corrections in Buenos Aires imply a greater variation in the National and Pampean Price indices of the one presented in the Province of La Pampa. We show that the CPI of the Patagonian Region is more representative of La Pampa than the CPI of the Pampean Region.